Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Fill in the blank in the following sequence:
[tex]\[
\begin{array}{l}
\left\{
\begin{array}{l}
f(1) = -3 \\
f(n) = -5 \cdot f(n-1) - 7
\end{array}
\right. \\
f(2) = \square
\end{array}
\][/tex]


Sagot :

To solve for \( f(2) \) given the recurrence relation:

[tex]\[ \begin{array}{l} f(1) = -3 \\ f(n) = -5 \cdot f(n-1) - 7 \end{array} \][/tex]

we need to follow these steps:

1. Identify the value of \( f(1) \):
[tex]\[ f(1) = -3 \][/tex]

2. Use the recurrence relation to find \( f(2) \):
[tex]\[ f(2) = -5 \cdot f(1) - 7 \][/tex]

3. Substitute the value of \( f(1) \) into the equation for \( f(2) \):
[tex]\[ f(2) = -5 \cdot (-3) - 7 \][/tex]

4. Simplify the multiplication:
[tex]\[ f(2) = 15 - 7 \][/tex]

5. Perform the subtraction:
[tex]\[ f(2) = 8 \][/tex]

Thus, the value of \( f(2) \) is:

[tex]\[ f(2) = 8 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.